Effect of Diabetes on Cortisol Levels After the Administration of Stenochlaena palustris (Burm.) Bedd - Helmi Susanti Simamora; Adi Prayitno; Muthmainah Muthmainah (Majalah Obat Tradisional, 2025)
Cortisol, is a steroid hormone, that plays a role as a stress hormone and is known to elevate blood sugar levels, leading to hyperglycemia. Hyperglycemia is characterized by high cortisol levels and insulin resistance in type 2 diabetes mellitus (T2DM). Kelakai (Stenochlaena palustris (Burm.) Bedd) has many health benefits, including its antioxidant content that can reduce blood sugar levels (hypoglycemia). This study aims to evaluate the cortisol level reduction in model rats with T2DM after being treated with Stenochlaena palustris (Burm.) Bedd extract by employing a laboratory experimental approach. The blood glucose analysis was performed using pre- and posttest control group designs, while the cortisol measurement followed a posttest control group design. The rats were divided into five groups: KN (normal group), K− (T2DM model rats) which became the control group in this research, K+ (T2DM model rats treated with metformin), and two experimental groups, namely, P1 and P2 (T2DM model rats treated with both metformin and kelakai extract at 400 and 800 mg/kgBW/day doses, respectively, administered through a nasogastric tube for 21 days). Statistics used parametric tests, namely, analysis of variance (ANOVA) with least significant difference post-hoc test. The results of the cortisol levels showed a significant difference (p ≤ 0.05).